2020
DOI: 10.3390/ma13102256
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Behaviors of Light Lanthanides(III) (La(III), Ce(III), Pr(III), Nd(III)) and Cr(III) Using Nitrolite

Abstract: The sorption of light lanthanides(III) (La(III), Ce(III), Pr(III), Nd(III)) and chromium(III) ions from acidic solutions on Nitrolite was studied at varying ions concentrations, pH, contact time and temperatures. The sorption capacity of lanthanides(III) and chromium(III) ions were examined in the ranges 2–9 and 2–5, respectively. The adsorption capacities of all metals are increase with the increasing pH (up to initial pH 9), despite the potential precipitation of metals at higher pH values. Therefore, an ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The prepared hydroxyapatite revealed adsorption efficiences of 0.25 mg/g for La(III) and 0.94 mg/g for Eu(III). Wójcik [ 40 ] studied the sorption of light lanthanides(III), i.e., La(III), Ce(III), Pr(III) and Nd(III)) on Nitrolite and the sorption capacities of La(III), Ce(III), Pr(III) and Nd(III) were 4.77 mg/g, 4.45 mg/g, 4.30 mg/g, 4.13 mg/g, respectively at pH 9. Analyzing the sorption capacity values of the above adsorbents, it was found that the synthesized ALG 5 L 1 composite exhibited a significant sorption potential towards the REE ions, the maximum sorption capacities at 333 K were equal to 109.56 mg/g for La(III), 97.97 mg/g for Ce(III), 97.98 mg/g for Pr(III), and 98.68 mg/g for Nd(III).…”
Section: Resultsmentioning
confidence: 99%
“…The prepared hydroxyapatite revealed adsorption efficiences of 0.25 mg/g for La(III) and 0.94 mg/g for Eu(III). Wójcik [ 40 ] studied the sorption of light lanthanides(III), i.e., La(III), Ce(III), Pr(III) and Nd(III)) on Nitrolite and the sorption capacities of La(III), Ce(III), Pr(III) and Nd(III) were 4.77 mg/g, 4.45 mg/g, 4.30 mg/g, 4.13 mg/g, respectively at pH 9. Analyzing the sorption capacity values of the above adsorbents, it was found that the synthesized ALG 5 L 1 composite exhibited a significant sorption potential towards the REE ions, the maximum sorption capacities at 333 K were equal to 109.56 mg/g for La(III), 97.97 mg/g for Ce(III), 97.98 mg/g for Pr(III), and 98.68 mg/g for Nd(III).…”
Section: Resultsmentioning
confidence: 99%
“…Lanthanide (Ln) elements have been studied extensively in diverse industrial applications of magnets, high-k gate dielectrics, display materials, catalysts, and batteries [1][2][3][4][5][6]. For recycling used Ln materials, various recovery methods for Ln elements have also been demonstrated [7][8][9][10][11][12][13]. In nuclear oxide fuels, Ln elements and actinide (An) elements are commonly co-present, and their redox behaviors are very similar.…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth (RE) elements have widely been used in diverse industry materials such as magnets, fluorescent lamps, catalysts, and batteries [ 1 , 2 , 3 , 4 , 5 ]. Lanthanide (Ln) elements are commonly co-present with actinide (An) elements in nuclear oxide fuels.…”
Section: Introductionmentioning
confidence: 99%